Genetic structure of the “Gaviluud” Mongolian sheep population - Ariuntuul, Tsendsuren; Tsendsuren, Tsedev (Proceedings of the Institute of Biology, 2022)
The genetic structure of the “Gaviluud” sheep population of Khanbogd Soum, Umnugovi Province was studied by polymorphism of the multilocus DNA AG-ISSR marker. A total of 24 fragments of the AG-ISSR-DNA marker were discovered in the study, and 83.33% of them were polymorphic. The genetic makeup of the “Gaviluud” sheep population, as revealed by polymorphism of the AG-ISSR-DNA marker, differed significantly from that of the “Saintsagaan” and “Darkhad” sheep populations. “Гавилууд” хонины сүргийн генетик тогтоц Өмнөговь аймгийн Ханбогд сумын “Гавилууд” хонины популяцийн генетик тогтцыг мултилокусын ДНХ-ийн AG-ISSR маркерын полиморфизмоор төлөөлүүлэн судлав. “Гавилууд” хонины популяцид AG-ISSR-DNA маркерын полиморфизмыг судлахад AG-ISSR-DNA маркерын 24 фрагмент тохиолдож байгаа ба AG-ISSR маркерын 83.33% нь полиморф байгааг илрүүлэв. “Гавилууд” хонины популяцийн AG-ISSR-DNA маркерын полиморфизмоор илэрхийлсэн генетик тогтоц “Сайнцагаан” болон “Дархад” үүлдрийн хониныхоос статистикийн хувьд бодитойгоор ялгаатай байв. Түлхүүр үгс: Монгол хонь, популяцийн генетик тогтоц, ДНХ-ISSR маркер, ДНХ-полиморфизм